(untitled) (IF-Sophia: revista eletrônica de investigações Filosófica, Científica e Tecnológica, 2014)
The Great War was celebrated on its outbreak. Writers on both sides helped to create and sustain the climate of celebration, although a few deplored the fact and wrote against it. In this paper, I will attempt to show the motivations behind support of the war, citing such factors as the enthusiasm of modernism for the supposed spiritual benefits of war and the inherited values of Victorian England, such as heroism and glory, embodied in popular literature and internalized by the men who went off to fight.